2020
DOI: 10.1002/bjs.11419
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic salpingectomy for prevention of ovarian cancer at the time of elective laparoscopic cholecystectomy

Abstract: Background Most serous ovarian cancers are now understood to originate in the fallopian tubes. Removing the tubes (salpingectomy) likely reduces the risk of developing high‐grade serous ovarian cancer. Numerous gynaecological societies now recommend prophylactic (or opportunistic) salpingectomy at the time of gynaecological surgery in appropriate women, and this is widely done. Salpingectomy at the time of non‐gynaecological surgery has not been explored and may present an opportunity for primary prevention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Concerns regarding the effect of opportunistic salpingectomy on subsequent ovarian function have not been substantiated by clinical data and the potential harm if any ought to be outweighed by the oncological benefits [18]. Indeed, the incidence of opportunistic salpingectomy in conjunction with hysterectomy appears to have increased substantially the past 10 years [19,20]. Recent studies indicate that women have a high acceptance for salpingectomy, also in combination with non-gynaecological procedures [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns regarding the effect of opportunistic salpingectomy on subsequent ovarian function have not been substantiated by clinical data and the potential harm if any ought to be outweighed by the oncological benefits [18]. Indeed, the incidence of opportunistic salpingectomy in conjunction with hysterectomy appears to have increased substantially the past 10 years [19,20]. Recent studies indicate that women have a high acceptance for salpingectomy, also in combination with non-gynaecological procedures [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the incidence of opportunistic salpingectomy in conjunction with hysterectomy appears to have increased substantially the past 10 years [19,20]. Recent studies indicate that women have a high acceptance for salpingectomy, also in combination with non-gynaecological procedures [20,21]. Several societies have issued statements supporting opportunistic salpingectomy at the time of hysterectomy on benign indications [22e24].…”
Section: Discussionmentioning
confidence: 99%
“…RRSO was performed in 100 patients due to BRCA mutations or high-risk personal or family history. An opportunistic salping(o-oophor)ectomy was performed in the remaining twelve patients with an isolated STIC during surgery for benign reasons (ovarian cyst, cholecystectomy) ( 12 , 34 36 ). In some cases, additional procedures were performed, mostly hysterectomies.…”
Section: Resultsmentioning
confidence: 99%
“…Ki-67 is a non-specific proliferation marker. An increased proliferative activity is usually defined as an overall Ki-67 expression of more than 10% of cells, but alternative systems, whereby the maximum proliferative index within a part of the lesion is taken, have also been proposed [12,69] One of the challenges with Ki-67 however is the high risk of interlaboratory variability. Polley et al compared staining of 100 breast tissue samples in eight different labs and concluded that cut-off values for Ki-67 for clinical decision making cannot be automatically transferred between laboratories [73].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…To also reduce ovarian cancer risk for low-risk women, an opportunistic salpingectomy can be considered under the appropriate circumstances. This means that the fallopian tubes are removed when a patient undergoes abdominal surgery for another benign indication [11,12]. Thirteen FIGO (International Federation of Obstetrics and Gynecology) member societies currently have statements regarding opportunistic salpingectomy, whereby a majority support considering this practice [13].…”
Section: Introductionmentioning
confidence: 99%